The Role Of Buildings Facades Of On Urban Landscape (Case Study: Old Context Of Sari) - Alishah, Majid; Ebrahimi, Abdollah; Ghaffari, Faezeh (The Turkish Online Journal of Design Art and Communication, 2016)
Facade and urban landscape, the dominant figure in the body of the city and containing the first messages in urbanism in the citizens’ outlook, has been a place of dialogue especially from the half of last century. The recognition of this theme its complex due to its’ close relationship with issue of identity and character of the city, and its’ scope was expanded with the beginning of the modern age and non-conventional management practices based on the law on urban development. In our society, urban landscape and face as a part of the country’s contemporary architecture conflict became as one of central focus of dialogue despite the specific cultural orientation of the system especially after the revolution and growth of population and urbanization share, war reconstructions, a massive expansion of cities in response to immigrant settlers and the expansion of higher education. * According to the purposes intended in this article, the method used in data collection method has been Library method and studying written documents. The content was analyzed using inductive reasoning method after data systematic and accurate foundation theoretical collection a and design of building facades in the old contexts of the city described. * The vulnerability of city spaces in front of inappropriate facades, in the design of buildings it should generally be noted that facades of buildings should be able to express the volume inside the building in addition to solidarity with public spaces. * So methodical design of facade and paying attention to ’riginality and beauty give the city identity and reduces the chaos of the city and thus turbulence of the people of city. This process leads to reconciliation of people with urban spaces and on the other hand prevents their remoteness from such places.
Keywords: Urban facades; old context; Sari